The PENGARUH KONSENTRASI KARAGENAN DAN SUHU PEMANASAN TERHADAP KARAKTERISTIK DAN ANTIOKSIDAN JELLY DRINK DAUN PEPAYA - Oka, Ni Made Ria; Ganda Putra, Gusti Putu; Kencana Putra, Nengah (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 7 No 2 (2020): Scientific Journal of Food Technology (September)DO - 10.24843/MITP.2020.v07.i02.p02, 2021)
Papaya leaf is one part of the papaya plant, which has benefits as an antioxidant. Development of papaya leaves into jelly drink products is expected to make it easier for people to enjoy drinks from papaya leaves and get health benefits. This study aims to determine the effect of carrageenan concentration and heating temperature on the characteristics and antioxidant activity of papaya leaf jelly drink, obtain the best carrageenan concentration and heating temperature to produce papaya leaf jelly drink, and obtain the stability of papaya leaf jelly drink to temperature during storage. This research used a factorial randomized block design. The first factor was carrageenan concentration consisting of three levels: 0.2; 0,4 and 0.6%. The second factor was the heating temperature, which consisted of three levels: 75 ± 2 o C, 85 ± 2 o C, and 95 ± 2 o C. The results showed that the concentration of carrageenan affected viscosity, brightness (L*), redness (a*), and yellowish level (b*) of papaya leaf jelly drink. The heating temperature affected the total phenol and antioxidant capacity of papaya leaf jelly drinks. The interaction of carrageenan concentration and heating temperature affected the color, texture, and overall acceptance of papaya leaf jelly drinks. The treatment did not affect the taste of the papaya leaf jelly drink. Carrageenan concentration of 0.2% and temperature of 75 ± 2 o C produced the best papaya leaf jelly drink with the following characteristics: 9000 cps viscosity, brightness level (L*) 20.30, redness level (a*) 9.73, levels yellowish (b*) 8.48, total phenol 7.12 mg/100g, antioxidant capacity 401.24 mg GAEAC/L, taste 2.4 (rather dislike), color 3.2 (normal), texture 3.2 (ordinary), and overall acceptance 2.9 (ordinary). The best storage temperature to maintain the stability of syneresis, total phenol, and antioxidant capacity of papaya leaf jelly drink was 10 o C.